2012
DOI: 10.3390/jfb3020398
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cell Mechanics from the Inside: Dispersed Single Wall Carbon Nanotubes Integrate with and Restructure Actin

Abstract: With a range of desirable mechanical and optical properties, single wall carbon nanotubes (SWCNTs) are a promising material for nanobiotechnologies. SWCNTs also have potential as biomaterials for modulation of cellular structures. Previously, we showed that highly purified, dispersed SWCNTs grossly alter F-actin inside cells. F-actin plays critical roles in the maintenance of cell structure, force transduction, transport and cytokinesis. Thus, quantification of SWCNT-actin interactions ranging from molecular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 60 publications
3
38
0
Order By: Relevance
“…Recently, an algorithmic approach was used to quantify filament length and number; however, this was validated using artificially generated filament networks. 25 In collaboration with CSIRO, we have developed an algorithm for analyzing actin cytoskeletal organization in a cell-based system using two tumor cell lines, the U2OS osteosarcoma cells and SK-N-SH neuroblastoma cells. These cell lines have been extensively studied and have a well-defined cytoskeleton, making them ideal for imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an algorithmic approach was used to quantify filament length and number; however, this was validated using artificially generated filament networks. 25 In collaboration with CSIRO, we have developed an algorithm for analyzing actin cytoskeletal organization in a cell-based system using two tumor cell lines, the U2OS osteosarcoma cells and SK-N-SH neuroblastoma cells. These cell lines have been extensively studied and have a well-defined cytoskeleton, making them ideal for imaging.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports in the literature by our group (Holt et al, 2010(Holt et al, , 2012c(Holt et al, , 2015Shams et al, 2014;Yaron et al, 2011) and others (Dulinska-Molak et al, 2014;Kaiser et al, 2008;Rodriguez-Fernandez et al, 2012;Sargent et al, 2012;Villegas et al, 2014;Zhang et al, 2011) that have shown high levels of cellular exposure to SWCNTs can alter subcellular components, including F-actin structures. Even though SWCNTs were present in X. laevis embryos at high local concentrations (up to~2 mg ml -1 ), there were no gross alterations to subcellular morphologies, including F-actin and endoplasmic reticulum.…”
Section: Nanotubes Are Subcellularly Localized In Perinuclear Regionsmentioning
confidence: 91%
“…Upon seeding, cells bind to fibronectin via cellular integrins and take up the geometry of the island. We selected the shape of our substrate islands based on previous traction force measurements in micropatterned cells [39][40][41]45 , which show that in cells constrained to a square shape, traction forces are highest at the vertices, moderately high at edges, and minimal in the middle of the cell (Fig. 3A).…”
Section: Piezo1 Ca 2+ Flickers Are Enriched At Regions Predicted To Hmentioning
confidence: 99%